Effectiveness of a fully immersive virtual reality-based therapeutic exercise programme with altered visual feedback in patients with fibromyalgia: A study protocol for a randomised controlled trial - Carlos Salvador-Huerta; Jaime Jordán-López; Pedro Azanon-Nogueira; Celia García-Lucas; Juan J. Amer-Cuenca; Juan Francisco Lisón (PLoS ONE, 2026)
Fibromyalgia (FM) is a chronic condition characterized by widespread pain, fatigue, and diverse physical and psychological symptoms that significantly impair daily functioning. Latest guidelines advocate for a comprehensive approach to FM management, emphasizing patient education, therapeutic exercise, pharmacological treatments, and psychotherapy. Although exercise remains the primary non-pharmacological strategy supported by robust evidence, its clinical implementation faces several limitations, including poor adherence, fear of movement, pain catastrophizing and proprioceptive deficits. Immersive virtual reality (IVR) has recently emerged as a promising adjunctive tool that not only addresses these limitations but also provides additional therapeutic benefits. Specifically, preliminary studies suggest that incorporating visual feedback manipulation through IVR can effectively modify movement perception, potentially enhancing clinical outcomes. This randomised controlled trial aims to assess the efficacy of a fully immersive virtual reality (FIVR)-based therapeutic exercise programme designed to induce implicit visual illusions, making participants perceive less movement than is performed during structured resistance exercises. Eighty participants diagnosed with FM will be recruited and randomly allocated to either the experimental group, which will engage in a structured resistance exercise regimen combined with FIVR, or the control group, performing identical exercises without FIVR. The primary measure will be the impact of FM on daily life, evaluated using the Revised Fibromyalgia Impact Questionnaire. Secondary outcomes include fatigue, sleep quality, FM symptom severity, health-related quality of life, psychological factors, central sensitization, body perception distortion, lower limb strength and handgrip strength, functional mobility, lumbar range of motion, influence of modified visual feedback, behavioural regulation during exercise and overall physical activity levels. This study aims to provide robust evidence regarding the potential benefits of integrating FIVR with therapeutic exercise. Findings could support FIVR as a valuable clinical innovation, potentially yielding superior improvements in daily functioning, physiological outcomes, and psychological well-being compared to traditional exercise interventions alone. ClinicalTrials.gov (NCT06948500). URL: https://clinicaltrials.gov/ct2/show/NCT06948500 .